Exploring the relationship between mathematical disposition, self-concept, and problem-solving ability in elementary school students - Salsabilla, Nulqia; Dewi Atma Junira; Diah Pahmasari Harahap; Siti Uswatun Khasanah; Ahmad Syaripudin; Lutfia, Afifa (Universitas Islam Raden Intan Lampung, INDONESIA, 2025)
Purpose: This study to examine the relationship between mathematical disposition and self-concept on elementary students’ mathematical problem-solving ability. The study is based on the assumption that problem-solving requires not only cognitive skills but also affective and psychological factors such as confidence, perseverance, curiosity, and students’ perceptions of their own abilities. Method: This study employed a quantitative ex post facto design involving 54 fifth-grade students selected through saturated sampling. Data were collected using a mathematical problem-solving test and Likert-scale questionnaires measuring mathematical disposition and self-concept. The data were analyzed using multiple linear regression with SPSS 25 to identify the influence of the two affective variables on problem-solving ability. Findings: The analysis showed that mathematical disposition and self-concept have a positive but statistically non-significant relationship with mathematical problem-solving ability. The coefficient of determination (R² = 0.038) indicates that both variables together contribute only 3.8 percent to students’ problem-solving performance, suggesting that other factors outside the study play a much larger role. Significance: The findings indicate that mathematical disposition and self-concept are not significant predictors of elementary students’ problem-solving skills. Other factors such as cognitive strategies, metacognitive skills, motivation, learning environment, and instructional approaches are likely to have greater influence. This highlights the need for future research exploring those variables and developing learning models that integrate affective development with higher-order thinking skills.